Mechano-regulatory cellular behaviors of NIH/3T3 in response to the storage modulus of liquid crystalline substrates. (April 2016) - Chen, Yang; Wang, Lei; Huang, Hao; Tan, Ruizhe; Zhao, Jupeng; Yang, Shenyu; Zeng, Rong; Wu, Hao; Zhang, Jiaqing; Yu, Bin; Tu, Mei
Abstract: The extent of substrate stiffness has been shown to be predominant in regulating cellular behaviors. Previous studies have used matrices such as elastomers or hydrogels to understand cell behavior. Herein, liquid crystalline matrices that resemble movable morphology of biomembrane and viscoelasticity were fabricated with tunable storage modulus for the evaluation of the modulus-driven cell behaviors. Our results demonstrated that NIH/3T3 cells showed a hypersensitive response to the storage modulus of liquid crystalline substrates by the alteration in attachment, spreading, proliferation and viability, polarization, cell cycle and apoptosis, and activity of mechano-transduction-related signal molecules including FAK, paxillin and ERK. The octyl hydroxypropyl cellulose substrates (OPC-1-5) with intermediate storage modulus of 12, 312 Pa and 7228 Pa (OPC-2 and OPC-3 respectively) could provide more beneficial adhesion conditions leading to a larger spreading area, more elongated morphology and higher proliferation rates possibly through paxillin-ERK pathway, whereas the substrates with the highest or lowest storage modulus (16, 723 Pa, OPC-1; and 41 Pa, OPC-5, respectively) appeared unfavorable for cell growth. Our study provides insights into the mechanism of modulus-driven cellular behaviors for better design of bioengineered cell substrates. Graphical abstract: Highlights: Novel type of liquid crystalline substrates (OPC) with tunable storage modulus were fabricated. OPC mimic in vivo extracellular matrix by exhibiting viscoelasticity and liquid crystalline state. NIH/3T3s were highly sensitive to the elasticity of OPC substrates. NIH/3T3s responded to mechanical stimuli of OPC substrates probably through paxillin-ERK pathway. OPC substrates with intermediate modulus facilitated cellular adhesion and proliferation.